User cost of debt-financed capital in Irish manufacturing industry: 1985-2011 - Nuša Žnuderl; Ide Kearney (The Economic and Social Research Institute (ESRI), 2013)
This paper provides estimates of the cost of debt-financed capital to Irish manufacturing industry over the period 1985 to 2011. The estimates are provided for two types of capital assets, machinery and equipment and industrial buildings. They also incorporate policy interventions aimed at influencing investment behaviour of manufacturing firms in Ireland. The results show that large capital gains recorded during the Celtic Tiger period created a downward distortion in the user cost of investing in industrial buildings. On average, policy interventions reduced the cost of capital compared to the cost of capital in the absence of these interventions, and the tax-related interventions were more favourable in the case of industrial building than for machinery and equipment.
Keywords: 330; cost of capital; manufacturing; Ireland; Celtic Tiger; capital gains; grants; taxation; allowances